Hypomethylation of long interspersed nucleotide element‐1 in peripheral mononuclear cells of juvenile systemic lupus erythematosus patients in China. (11th December 2013) - Huang, Xiaolan; Su, Gaixiu; Wang, Zhen; Shangguan, Shaofang; Cui, Xiaodai; Zhu, Jia; Kang, Min; Li, Shengnan; Zhang, Ting; Wu, Fengqi; Wang, Li
Abstract Aim Methylation abnormalities in T lymphocytes have been reported to correlate with systemic lupus erythematosus (SLE). Previous studies identified hypomethylation in the promoter of several genes linked to SLE. Long interspersed nucleotide element‐1 (LINE‐1) constitutes 17–25% of the human genome, and LINE‐1 hypomethylation has been reported in SLE. Limited information is available regarding LINE‐1 methylation in juvenile SLE (JSLE). Method Methylation levels of LINE‐1 in peripheral blood mononuclear cells (PBMCs) from 59 JSLE and 47 control samples were examined by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry. Total homocysteine (tHcy) concentrations in plasma were measured by immunoassay. Results Significant hypomethylation of LINE‐1 was observed in PBMCs from JSLE patients (60.93% in cases compared with 62.88% in controls, P = 0.001). Significant LINE‐1 hypomethylation was observed in active SLE compared to controls (60.66% vs. 62.88%, P = 0.001). According to other clinical parameters, a significant correlation was found between LINE‐1 methylation levels and the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI‐2000) of the cases (r = −0.285, P = 0.032). The risk of JSLE increased with decreasing levels of LINE‐1 methylation, with an odds ratio of 14.5 (95% CI: 2.8–75.6, P = 0.002). Cases had significantly higher plasma concentrations of tHcy than controls (15.11 vs. 11.02 μmol/L, P = 0.028); the correlation between LINE‐1 methylation levels and tHcy was significant (r = −0.4, P = 0.013). Correlations between methylation levels of LINE‐1 and complement component 3 were significant (r = 0.317, P = 0.044; r = 0.387, P = 0.031, in total JSLE and active JSLE, respectively). Conclusion Hypomethylation of LINE‐1 is associated with risk of JSLE, and LINE‐1 methylation levels were related to disease activity and clinical manifestations. The correlation between tHcy levels and LINE‐1 methylation was significant.